The footprints of history: path dependence in the transformation of property rights in Kenya’s Maasailand. - Mwangi, Esther (Cambridge University Press, 2006)
The recent wave of subdivision of Maasai group ranches is not an isolated event, but rather part of a broader, historical process of transformation in land relations and policy development in Maasailand. Maasai have over time supported land privatization, first by formalizing collective rights in group ranches and more recently by individualizing collective land holdings. Privatization is perceived to be an effective strategy for safeguarding Maasai land claims against appropriation by non-Maasai, the government and elite Maasai. Construction of the Uganda railway in early twentieth century and the subsequent influx of European settlers who were granted individual title to secure their investments are events that began the institutional path of privatization. The persistence and dominance of individualized arrangements regardless of other more optimal property rights options is a result of the dominance of elite interests (supported by state institutions) even as state imposed institutions replaced Maasai customary systems of land allocation.